Sustainable Civilization - Egmond, Klaas van.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
In order to be sustainable, a civilization must maintain the balance between 'mind' and 'matter' and between the egocentric 'I' and 'the others'. This book investigates how new institutional arrangements in politics, economy and finance can resolve the current crisis of social values by restoring this delicate balance between opposing forces.
Keywords: Development economics; Economic development; International relations; Economic policy; Political science; Sustainable development; Development Economics; Development Studies; International Relations; Development Policy; Political Science; Sustainable Development